Sleep loss and addiction. (October 2022) - López-Muciño, Luis Angel; García-García, Fabio; Cueto-Escobedo, Jonathan; Acosta-Hernández, Mario; Venebra-Muñoz, Arturo; Rodríguez-Alba, Juan Carlos
Abstract: Reducing sleep hours is a risk factor for developing cardiovascular, metabolic, and psychiatric disorders. Furthermore, previous studies have shown that reduction in sleep time is a factor that favors relapse in addicted patients. Additionally, animal models have demonstrated that both sleep restriction and sleep deprivation increase the preference for alcohol, methylphenidate, and the self-administration of cocaine. Therefore, the present review discusses current knowledge about the influence of sleep hours reduction on addictivebehaviors; likewise, we discuss the neuronal basis underlying the sleep reduction-addiction relationship, like the role of the orexin and dopaminergic system and neuronal plasticity (i.e., delta FosB expression). Potentially, chronic sleep restriction could increase brain vulnerability and promote addictive behavior. Graphical Abstract: ga1 Highlights: The reduction of sleep hours in contemporary society can be a factor that facilitates the consumption of addictive substances. Orexins' overstimulation of VTA neurons due to prolonged wakefulness leads to sensitization of the reward circuit. Sleep loss potentially detonates neuronal plasticity that facilitate the development of addictive behavior.